2014
DOI: 10.1371/journal.pone.0101672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Induction of Immune Memory following Infant Immunisation with Serogroup C Neisseria meningitidis Conjugate Vaccines – Exploratory Analyses within a Randomised Controlled Trial

Abstract: AimWe measured meningococcal serogroup C (MenC)-specific memory B-cell responses in infants by Enzyme-Linked Immunospot (ELISpot) following different MenC conjugate vaccine schedules to investigate the impact of priming on immune memory.MethodsInfants aged 2 months were randomised to receive 1 or 2 doses of MenC-CRM197 at 3 or 3 and 4 months, 1 dose of MenC-TT at 3 months, or no primary MenC doses. All children received a Haemophilus influenzae type b (Hib)-MenC booster at 12 months. Blood was drawn at 5, 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The significantly greater number of Men C- and Men Y- specific memory B cells at M7 compared to M6 is likely reflective of the time of blood sampling post vaccination, where M6 samples are 2 months following the previous dose of vaccine and M7 are 1 month post the previous dose of vaccine. Whilst a recent study comparing several Men C glyco-conjugate vaccines has shown an increase in the number of memory B cells from post-prime to pre-boost [ 12 ], we have not seen this in our study. This could be due to differences in the vaccines used, or the length of time between post-prime and pre-boost time-points.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The significantly greater number of Men C- and Men Y- specific memory B cells at M7 compared to M6 is likely reflective of the time of blood sampling post vaccination, where M6 samples are 2 months following the previous dose of vaccine and M7 are 1 month post the previous dose of vaccine. Whilst a recent study comparing several Men C glyco-conjugate vaccines has shown an increase in the number of memory B cells from post-prime to pre-boost [ 12 ], we have not seen this in our study. This could be due to differences in the vaccines used, or the length of time between post-prime and pre-boost time-points.…”
Section: Discussioncontrasting
confidence: 84%
“…A number of studies in animal models have identified that B cells primed at initial antigen encounter can become either memory B cells or plasma cells, the latter of which are terminally differentiated and short- or long- lived [ 4 , 5 ]. In studies of glyco-conjugate vaccines, polysaccharide-specific plasma cells [ 6 ] and memory B cells [ 6 12 ] have been measured in the peripheral blood following priming and booster doses, and two studies in infants have identified that Men C-specific memory B cells present post-priming are good predictors of the persistence of Men C-specific IgG at 12 months prior to boosting [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, priming with a single MenC-CRM dose induced higher post-Hib-MenC-TT rSBA geometric mean titres than two priming doses, suggesting that the administration of a greater amount of MenC antigen during priming reduces the subsequent immune response to the 12 month MenC conjugate vaccine booster dose. The underlying mechanism, which is not reflected in the frequencies of MenC-specific memory B cells in peripheral blood detected at 5, 12, or 13 months,20 could still be related to differences in numbers of memory B cells if the pool is considered to be resident in lymphoid tissues and therefore inaccessible with peripheral blood sampling. Furthermore, this phenomenon might be the result of dose dependent differences in carrier protein that manifest when different MenC glycoconjugate vaccine formulations are used for priming and boosting.…”
Section: Discussionmentioning
confidence: 99%
“…The memory B cells measured by ELISpot in the peripheral blood at 5 months of age following a single dose of NeisVac-C Ò at 3 months of age were compared to 2 doses of Menjugate Ò at 3 and 4 months of age. 19 Responses following a booster dose, showed significantly higher SBA GMTs following boosting in those primed with a single dose of NeisVac-C Ò at 3 months of age compared to 2 doses of Menjugate Ò at 3 and 4 months of age. Children who had been primed with NeisVac-C Ò produced the greatest memory B cell response to the Menitorix Ò booster.…”
Section: Evidence Supporting a Single Infant Priming Dosementioning
confidence: 96%
“…18,19 Infants were vaccinated with a single dose of either Menjugate Ò or NeisVac-C Ò at 3 months of age, compared to 2 doses of Menjugate Ò at 3 and 4 months of age. Blood samples collected at 5 months of age, showed the SBA GMT to be significantly higher in the 2 dose Menjugate Ò group (GMT of 618.3 (95%CI 538.3-710.1), compared to 53 (95%CI 39.9-70.5) and 155.4 (95%CI 112.3-213.8) in those who received one dose of Menjugate Ò or NeisVac-C Ò , respectively.…”
Section: Evidence Supporting a Single Infant Priming Dosementioning
confidence: 99%